EMC aspects of compact wiring for future aircraft - Lansink Rotgerink, J.H.G.J.; Schippers, H.; Verpoorte, J.; Nuyten, K. (IEEE, 2018)
The installation of wiring in future aircraft will become a big challenge. Available space for wiring will decrease, while the amount of wiring will increase, since more and more aircraft systems will be electronically driven instead of hydraulically. It is proposed to make wiring systems more compact. The aim of this paper is to investigate EMC aspects of this compact wiring by simulations and measurements in a representative part of a smart wing of a future aircraft.